Percival Everett’s The Water Cure: A Blind Read - Anne-Laure Tissut (Sillages Critiques)
In his 2007 novel The Water Cure, Percival Everett explores and explodes representation through language so as to offer the reader a radical experience of questioning her expectations in reading and more generally her reading processes together with her language habits. The interplay of the twin notions of exposure and overexposure allows to approach the dismantlement of language taking place in The Water Cure, that brings out the wealth of language potentials as well as the constant threat to which communication is subject. The exploration and questioning carried out by Everett call for new ways of reading and writing literary criticism.